''فتح الرحمٰن فی اثبات مذہب النعمان''کا تحقیقی و تجزیاتی مطالعہ: An Analytical study of the "Fath-ur-Rehman Fi Ithbāt-e-Madhab al-Naumān" - Nawaz, Muhammad; Fareed ud din, Hafiz (Al-Amīr Research Journal for Islamic Studies, 2021)
In "Fath-ur-Rehman Fi Ithbāt-e-Madhab al-Naumān", Shaykh Abdul Haq Muhaddith Dehalvi collected Ahadith supporting the religion and sect of Imam Abu Hanifa (R.A) and described the differences of the jurists and gave preference to Hanafi School of thought. He has proved through this book that Imam’s sect is in accordance with the Sahih Ahadith and while removing the accusations leveled against Imam Abu Hanifa, he declared that these are the issues on which the contrariness of the hadith was accused but irony of the situation is that Abu Hanifa (R.A) is following the hadith while other jurists explicitly base their intellect and conjecture and the style of the book shows that Abu Hanifa (R.A) is the absolute doer of hadith and Imam Shafi (R.A) uses conjecture and opinion. Moreover, Author speaks on the authenticity of the hadiths which not only support him but also give comfort and consolation to the opposing party. This great book of Hazrat Shaykh Muhaddith (R.A) is unique and unique in its importance, infrequency, style of reasoning, research issues, preference of religion, and hadiths supporting Hazrat Imam Azam Abu Hanifa (R.A) which opens new chapters of coming research. In the said article, an analytical study of his book "Fath-ur-Rehman fi Asbat-e-Madhhab-e-Noman" will be presented which will expose the reality of Imam Abu Hanifa's accusation of being against the hadith and this great effort of Sheikh Abdul Haq will also be brought to light.